Modelling Growth Curves In Kampung Super Garut Chicken Fed With Pasak Bumi Meal (Euricoma longifolia Jack) - Abdul Kholik; H. Indrijani; W. Tanwiriah (Jurnal Ilmu Ternak, 2019)
AbstractChicken growth will be showing a curve with certain mathematic model. The aim of this research was to predict growth curve model of kampung super garut chicken Fed With Pasak Bumi Meal (Euricoma longifolia Jack). This research used descriptive eksperimental method with 100, divided in five groups. Every groups fed with Pasak Bumi Meal in five categories is R0 (0%), R1 (0,025%), R2 (0,050%), R3 (0,075%) and R4 (0,100%). Chickens reared for 12 weeks, the collected data is body weight and body weight gain. Scatter plots data is used for estimated determination coefficient (R2), correlation coefficient (r), and standard error (SE). The results showed that; (1) addition of pasak bumi flour in ration at level 0,075% in ration resulted growth performance optimal; (2) The Gompertz model with the formula of  Y = 1965.2 exp (-3.7890e-0.1456t ) was the best model with coefficient determination (R2) of 99.94%, coefficient of correlation (r) of 99.97%, and standard error (SE) of 16.01%. (3) growth rate until 12 weeks ages still increase.